Introduction to light trapping in solar cell and photo-detector devices - Fonash, S. J. (London : Elsevier, 2015)
Discusses the use of photonic and plasmonic effects for light trapping in solar cells. This book compares and contrasts texturing, the method of light-trapping design in solar cells, with emerging approaches employing photonic and plasmonic phenomena.
Machine generated contents note: ch. 1 A Brief Overview of Phenomena Involved in Light Trapping -- 1.1.Interference -- 1.2.Scattering -- 1.3.Reflection -- 1.4.Diffraction -- 1.5.Plasmonics -- 1.6.Refraction -- ch. 2 Modes and Hybridization -- 2.1.Introductory Comments -- 2.2.Radiation Modes -- 2.3.Trapped Traveling Modes: Guided Modes -- 2.4.Trapped Traveling Modes: Bloch Modes -- 2.5.Trapped Localized Modes: Mie Modes and Plasma Modes -- ch. 3 Light-Trapping Structures -- 3.1.Introduction -- 3.2.Planar Structures with ARCs -- 3.3.Planar Structures with Randomly Textured Surfaces -- 3.4.Structures with Nanoelement Arrays -- 3.5.Structures with Plasmonic Effects -- ch. 4 Summary -- 4.1.The Current Picture -- 4.2.Some Future Directions? -- 4.3.Overview.
engineering bookfair2015
Includes bibliographical references: (p. 63-65)
Keywords: Solar energy; Silicon crystals; Solar cells; Optical detectors; Photovoltaic power systems; Electric power-plants.